Purchase Decisions on Rockland Bogor Convection T-Shirts - Masayu, Baby Panca; Maulana, Lucky Hikmat; Yulianingsih; Andari, Titiek Tjahja (MultiTech Publisher, 2023)
This study aims to analyze and identify the effect of price perceptions and promotions simultaneously or partially on purchasing decisions of Rockland Screen Printing Convection T-Shirts. Questionnaires were distributed to 60 respondents using purposive sampling technique with the following criteria; 1) consumers have purchased Rockland Screen Printing products at least 2 times, 2) consumers are at least 17 years old. Data collection was carried out through a questionnaire. The analytical method uses descriptive and verification methods through multiple correlation, multiple regression, coefficient of determination, F test and t test. The results showed that the perceived price and promotion variabels simultaneously or partially had a positive and significant effect on the purchasing decision of the Rockland Screen Printing Convection T-Shirt.